Spatial Lifecourse Epidemiology Reporting Standards (ISLE-ReSt) statement. (January 2020) - Jia, Peng; Yu, Chao; Remais, Justin V.; Stein, Alfred; Liu, Yu; Brownson, Ross C.; Lakerveld, Jeroen; Wu, Tong; Yang, Lijian; Smith, Melody; Amer, Sherif; Pearce, Jamie; et al.
Abstract: Spatial lifecourse epidemiology is an interdisciplinary field that utilizes advanced spatial, location-based, and artificial intelligence technologies to investigate the long-term effects of environmental, behavioural, psychosocial, and biological factors on health-related states and events and the underlying mechanisms. With the growing number of studies reporting findings from this field and the critical need for public health and policy decisions to be based on the strongest science possible, transparency and clarity in reporting in spatial lifecourse epidemiologic studies is essential. A task force supported by the International Initiative on Spatial Lifecourse Epidemiology (ISLE) identified a need for guidance in this area and developed a Spatial Lifecourse Epidemiology Reporting Standards (ISLE-ReSt) Statement. The aim is to provide a checklist of recommendations to improve and make more consistent reporting of spatial lifecourse epidemiologic studies. The STrengthening the Reporting of Observational Studies in Epidemiology (STROBE) Statement for cohort studies was identified as an appropriate starting point to provide initial items to consider for inclusion. Reporting standards for spatial data and methods were then integrated to form a single comprehensive checklist of reporting recommendations. The strength of our approach has been our international and multidisciplinary team of content experts and contributors who represent a wide range of relevant scientific conventions, and our adherence to international norms for the development of reporting guidelines. As spatial, location-based, and artificial intelligence technologies used in spatial lifecourse epidemiology continue to evolve at a rapid pace, it will be necessary to revisit and adapt the ISLE-ReSt at least every 2–3 years from its release. Highlights: Spatial lifecourse epidemiology can enable us to advance health geography research. There have not been any reporting guidelines for health geography or spatial epidemiologic studies. This guideline is made from a consensus of multidisciplinary experts. This guideline can improve the quality of reporting of spatial lifecourse epidemiologic studies.